Development of a behavioral measurement of sensation seeking personality trait and its association with negative health outcomes - DiCecco, Samuel M., author; Seger, Carol, advisor; Conner, Brad, advisor; Davies, Patti, committee member; Karoly, Hollis, committee member (Colorado State University. Libraries, 2024)
Sensation seeking, a personality trait in which an individual has the tendency to pursue novel and highly stimulating experiences and often engages in risky behaviors to do so, is associated with several negative health outcomes when paired with low cognitive control. These outcomes include higher rates of substance misuse, self-harm, problem gambling, risky sexual behavior, engaging in dangerous sports, and criminal activities. It would be beneficial to have valid ways of measuring the trait to address or prevent these negative health outcomes from occurring. The sensation seeking personality trait is typically only measured using self-report surveys, even though it manifests itself behaviorally. Creation of behavioral measurements of sensation seeking may aid in the understanding of the trait and its behavioral effects, as well as aid in prevention of negative health outcomes. Previous attempts to measure sensation seeking behaviorally have not been successful, potentially due to the inherent nature of the trait being difficult to elicit in standard laboratory tasks and environments, and use of extrinsic rather than intrinsic motivators. I developed two novel emergent behavioral tasks to measure observed changes in participant-driven behavior and related these task variables to each individual's measured sensation seeking personality trait. I also assessed whether these new task measures correlated with reported negative health behaviors that have been associated with sensation seeking. This dissertation consists of three studies utilizing these novel emergent behavioral tasks. The first compared task measures to self-report measures of sensation seeking and personality traits, the second served as a replication and looked at relations between task measures and risky behaviors, and the third developed a virtual reality variant of the tasks. Several of the behavioral measurements within the emergent behavior tasks showed significant relations with sensation seeking personality trait, in particular measures of risky or "dangerous" decisions made in Studies 1 and 2 that correlated with the risk seeking subtype of sensation seeking personality trait. Study 3 found that implementing the behavioral tasks in virtual reality resulted in weaker, rather than stronger, relationships between the behavioral measures and self-report measures. Together, these studies found that the emergent tasks implemented using standard computer interfaces, but not virtual reality, show promise as valid behavioral measurements of sensation seeking personality trait.
Keywords: emergent behavior; sensation seeking; virtual reality; risky behavior; behavioral measurement; substance use